Implementing digital technology in the New Zealand Curriculum - Fox-Turnbull, Wendy (Australasian Journal of Technology Education, 2019)
This article initially reviews literature that argues for a place for digital technologies in the curriculum. Understanding of and competency in developing digital technologies is becoming an increasingly debated topic around the world. Areas of debate include where and when key components of digital literacy such as computational thinking, computer science, programming, and coding should be learned. This article argues for the inclusion of digital technologies in the curriculum and more specifically within the technology curriculum. A case study of the decision-making process of New Zealand as it moves to include digital technologies into The New Zealand Curriculum in subsequently presented. An account of the processes undertaken by the New Zealand Ministry of Education to include and implement digital technologies in technology education is presented. Finally, it offers a cautionary warning about two potential risks as New Zealand enters the implementation phase of its new digital technologies curriculum.